DIRĀSAH MANHAJ AL LUGHAH AL ‘ARABIYYAH FÎ MA’HAD AL FALĀH LI AL BANĀT - Fazrina, Diah; Muradi, Ahmad (STIQ Amuntai, 2020)
This study reveals the Arabic learning curriculum at Al-Falah Islamic Boarding school. As a Salafi boarding school, the curriculum used by al-Falah in learning Arabic is a number of plans and materials used by the teacher for students in learning Arabic is a boarding school environment. The learning experience in Arabic is more dominant given in the form of Islamic studies through reading yellow books or Arabic texts without lines. The experience is in accordance with the vision and mission of the cottage that is providing religious knowledge with both fardhu ain and fardhu kifayah, also knowledge and technology and independent. But in addition, this lodge also applies the curriculum of the year 2013 from the Ministry of Religion for students. The material referred to here is a list of subjects. Related to Arabic, the material provided into various subjects such as nahwu, sharf, balaghah, tafsir, tajwid, and others. The method used by the most dominant teachers is Qawaid and Tarjamah or Structure and Translation and other methods according to the material being taught. The evaluation used is a written test and an oral test. Keywords: Salafi Islamic Boarding School, Curriculum and Arabic Language